Understanding Poverty from the Development of Unemployment and Illiteracy Rates - Fernando Saragih; Anggita Vanesa Liunima; Indra M Pratama; Emilia Gie; Julio Ardilo Benu; Jibrael Mau; Elviani Adelia Detha; Marghenete Nedelin Snae (Jurnal Inovasi Pendidikan Ekonomi, 2025)
Poverty is a crucial problem that can affect various aspects of society. The large contribution of this variable is the basis for carrying out this research. Based on the theory, poverty itself is related to the illiteracy rate (IR) and unemployment, where these two factors can determine the conditions of poverty. In the research, NTT province was one of the research locations. This is based on economic conditions, where NTT is in the top 5 provinces with the highest levels in Indonesia. This research used secondary data for 18 years. Based on the data that has been collected and data quality tests (classical assumptions), results were obtained showing that unemployment and illiteracy rate have a positive and significant influence. Based on this picture, improving training and the quality of education is the right key to eradicating poverty